2022
DOI: 10.1109/tps.2022.3210995
|View full text |Cite
|
Sign up to set email alerts
|

Voltage–Current Characteristic of Free Burning Arcs in SF₆ Alternative Gas Mixtures

Abstract: Voltage-current characteristics of free burning arcs in SF6 and air have been known for decades. As the demand for an SF6-free solution is increasing, there is an accompanying need to determine arc parameters in the alternative gases. An unblown arc experiment has been established to determine the voltagecurrent characteristics of SF6 alternative gases, which have not yet been thoroughly studied. In this experiment free burning arc measurements were performed in a number of gases under consideration of SF6 alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It is likely that many other factors are influencing the decomposition rates, like the arc temperature, usually linked to the current density. The performed experiment is however reproducing conditions closer to some switching duties in disconnectors [4] in terms of geometry. Applicability to bus-transfer switching, described in IEC 62271-102, is possible but dependent on the correct equivalences between the experiment and the type-tests.…”
Section: E Discussion On Gas Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…It is likely that many other factors are influencing the decomposition rates, like the arc temperature, usually linked to the current density. The performed experiment is however reproducing conditions closer to some switching duties in disconnectors [4] in terms of geometry. Applicability to bus-transfer switching, described in IEC 62271-102, is possible but dependent on the correct equivalences between the experiment and the type-tests.…”
Section: E Discussion On Gas Resultsmentioning
confidence: 94%
“…As a result of the arc-driven decomposition of the gases, only an insignificant pressure increase was observed, which was not included in the analysis. A more detailed description of the experiment can be found in the article by Pietrzak et al [4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 These parameters also affect the insulating ability of C 4 F 7 N. For example, as the distance between the arc contacts in a circuit breaker increases, the insulating efficiency of the gas is improved. 39 It was also found that the breakdown voltage for mixtures of 20% C 4 F 7 N and 80% CO 2 follows a nonlinear pattern as pressure increases. 40 When it comes to general-purpose chemical trace analysis, GC has been the default laboratory technique for separating and analyzing mixtures.…”
Section: ■ Backgroundmentioning
confidence: 95%